Heterogenität und Bildungsmedien - Aamotsbakken, B.; Matthes, E.; Schütze, S. (2017)
There are several very useful essays in this anthology. I particularly liked: - Wiater, Werner: "Indvidualized Teaching as solution of the problem of heterogeneity!? Learning "à la carte" becomes digital learning." Also talks about limits of individualized teaching. - Heiland Thomas: "Supporting non-German children in a heterogenous context of education." Concentrates on curricula and gives many examples of how to incorporate digital media in the multilingual classroom. - Ascherl, Carina und Anja Ballis: "Learning with multilingual Online material. Possibilities of approaching linguistic heterogeneity with multilingual media." Focusses on German as a Foreign Language, names many multilingual sources for material